1997
DOI: 10.2134/agronj1997.00021962008900010011x
|View full text |Cite
|
Sign up to set email alerts
|

Winter Rye as a Cover Crop Following Soybean under Conservation Tillage

Abstract: rye cover crop following soybean to increase the amount of winter and spring surface residue cover prior to plant-Use of a winter rye (Secale cereale L.) cover crop following soybean ing and during the seedbed and establishment phase of [Glycine max (L.) Merr.] has been shown to reduce the soil erosion potential in a corn (Zea mays L.)-soybean rotation system, but little the corn year. They demonstrated that regardless of is known about the effect of rye on residual soil NO 3 -N (RSN). An tillage management or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 12 publications
7
64
1
Order By: Relevance
“…These results confirm several reports of lower soil nitrate-N content at various locations in the soil profile under NT compared with CT (Angle et al, 1993;Dou et al, 1995;Kessavalou and Walters, 1999).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results confirm several reports of lower soil nitrate-N content at various locations in the soil profile under NT compared with CT (Angle et al, 1993;Dou et al, 1995;Kessavalou and Walters, 1999).…”
Section: Resultssupporting
confidence: 92%
“…This compares with 78 AE 67 kg N ha À1 within the 0-120-cm profile of a Typic Hapludult in Pennsylvania (Dou et al, 1995), 143 AE 51 kg N ha À1 Table 2 Soil nitrate (NO 3 )-N as affected by tillage (CT, conventional tillage and NT, no tillage), cover crop management (ungrazed and grazed), and soil-profile zone (0-40 cm is the upper rooting zone, 40-90 cm is the lower rooting zone, and 90-150 cm is below the typical rooting zone) at the end of 1, 2, 3, 4, and 6 years of evaluation. within the 0-150-cm profile of a Typic Argiudoll in Nebraska (Kessavalou and Walters, 1999), and 457 AE 176 kg N ha À1 within the 0-210-cm profile of Udic Argiustoll/Udertic Paleustoll in Oklahoma (Raun and Johnson, 1995). Rate of change in soil nitrate-N content varied significantly by cropping system and tillage regime, and to a much lesser extent cover crop management (Table 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Decreases in total soil mineral N contents in the WCC plots indicated uptake of soil NO 3 -N into WCC bio- mass. Kessavalou and Walters (1999) observed that measured cereal rye N uptake was nearly equivalent to observed reductions in spring residual soil NO 3 -N. Similar soil NO 3 -N reductions with delay in kill date of cereal rye WCC were observed in both fertilized (early N split) and unfertilized (late N split) rye. However, the application of N-fertilizer during cereal rye growth (early N split) improved soil NO 3 -N content at planting across all kill date treatments.…”
Section: Discussionsupporting
confidence: 62%
“…However, research has found differing annual crop yield responses with RCC. Corn grain and silage yield decreases have been reported with use of RCC (Raimbault et al, 1990;Kessavalou and Walters, 1997;Thelen and Leep, 2002;Singer and Kohler, 2005;McDonald et al, 2008;Kramberger et al, 2009;Salmerón et al, 2011;Krueger et al, 2012;Reese et al, 2014). A 15% corn yield increase was observed in 2 out of 3 yr in a study conducted on sandy soils in Wisconsin with no N application to the RCC and with low RCC biomass production .…”
mentioning
confidence: 99%